Allergies in urban versus countryside settings in Poland as part of the Epidemiology of the Allergic Diseases in Poland (ECAP) study – challenge the early differential diagnosis - Krzych-Fałta, Edyta; Furmańczyk, Konrad; Piekarska, Barbara; Tomaszewska, Aneta; Sybilski, Adam; Samoliński, Bolesław K. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction: The incidence of allergies depends on a number of factors, including adopting an urban “western” lifestyle, genetic predispositions, and different regions of residence. Aim : To compare the prevalence of allergic conditions (seasonal allergic rhinitis (SAR) and perennial allergic rhinitis (PAR), bronchial asthma (BA), atopic dermatitis (AD)) in a group of countryside versus urban residents in Poland. Material and methods : The prevalence of allergic conditions in urban versus countryside settings was assessed using the translated and approved questionnaire developed for international ECRHS II and ISAAC studies. Respondents were selected via random multistage sampling, with proportionate stratified sampling, and the Polish Resident Identification Number (PESEL) as the basis. A total of 18,617 respondents took part in the study. Subsequently, approximately 25% of the subjects underwent outpatient assessments: skin-prick, lung function, peak nasal inspiratory flow (PNIF) tests, as well as history-taking. Results : Allergic rhinitis (AR) proved to be the most common condition in the entire study population. Children residing in the countryside were twice more likely to be diagnosed with BA (8.33% vs. 4%; p < 0.05). Conversely, in the adult subgroup, BA was more commonly observed in urban areas. Whereas reported symptom rates were much higher in AR and AD patients, symptomatic BA was proportionately lower with respect to the official diagnoses (underdiagnosed BA phenomenon). Atopic dermatitis was considerably more common in the metropolitan population. One factor that significantly correlated with allergic diseases was a positive family history. Conclusions : Inhabitants of metropolitan areas are to a greater extent predisposed to allergic conditions. One factor significantly contributing to allergies is genetic predisposition. Given the scale of the problem, there is an urgent need to implement measures for early prevention and diagnosis of allergies to minimize distant health effects.